Controllable inverse design of auxetic metamaterials using deep learning. (1st December 2021) - Zheng, Xiaoyang; Chen, Ta-Te; Guo, Xiaofeng; Samitsu, Sadaki; Watanabe, Ikumu
Graphical abstract: Highlights: We propose an inverse design method for auxetic metamaterials using deep learning. We designed novel 2D auxetic metamaterials based on Voronoi tessellation for the training dataset. The trained neural network can generate 2D auxetic metamaterials with user-desired Young's moduli and Poisson's ratios. The proposed method can easily be extended to the inverse design of other architected materials. Abstract: As typical mechanical metamaterials with negative Poisson's ratios, auxetic metamaterials exhibit counterintuitive auxetic behaviors that are highly dependent on their geometric arrangements. The realization of the geometric arrangement required to achieve a negative Poisson's ratio relies considerably on the experience of designers and trial-and-error approaches. This report proposes an inverse design method for auxetic metamaterials using deep learning, in which a batch of auxetic metamaterials with a user-defined Poisson's ratio and Young's modulus can be generated by a conditional generative adversarial network without prior knowledge. The network was trained based on supervised learning using a large number of geometrical patterns generated by Voronoi tessellation. The performance of the network was demonstrated by verifying the mechanical properties of the generated patterns using finite element method simulations and uniaxial compression tests. The successful realization of user-desired properties can potentially accelerate the inverse design and development of mechanical metamaterials.